U-Pb Age, Setting and Tectonic Significance of the Anorthosite-Mangerite-Charnockite-Granite Suite, Lofoten-Vesteralen, Norway - CORFU, F. (Journal of Petrology, 2004)
Mangerites, charnockites, anorthosites, gabbros and granites occur within a high-grade metamorphic complex in the Lofoten-Vesterålen islands of northern Norway. U-Pb dating of zircon, titanite and monazite indicates a three-stage magmatic history beginning at 1870-1860 Ma with the emplacement of the Lødingen and Hopen plutons, followed by a dominant stage at 1800-1790 Ma that formed the bulk of the suite, and concluded by the emplacement of pegmatites, local rehydration and retrogression between 1790 and 1770 Ma. On the scale of the Baltic Shield the 1870-1860 Ma episode corresponds to contraction, amalgamation of arcs, and regional deformation. By contrast, the episode at 1800-1790 Ma was characterized by major shifts in plate convergence, by intraplate deformation, and by a diversity of magmatic associations including suites derived from the subcontinental mantle and widespread granitoid rocks extracted from the continental crust. The diversity of concurrent magmatic events across the Svecofennian orogen, and the temporal coincidence with collisional events in coeval orogenic belts, suggests that the genesis of the suite of magmatic rocks may have been related to tectonically driven mechanisms of magma generation.